Yield response and economic performance of participatory evaluated elite vegetable cultivars in intensive farming systems in Tanzania - Lukumay, Philipo J.; Afari-Sefa, Victor; Ochieng, J.; Dominick, I.; Coyne, Danny L.; Chagomoka, Takemore (International Society for Horticultural Science, 2018)
Yield response and economic performance of farmer selected and preferred elite tomato (Lycopersicon esculentum 'Tengeru 2010'); African eggplant (Solanum aethiopicum 'Tengeru white') and amaranth (Amaranthus cruentus 'Madiira I') cultivars were undertaken in four communities located in Babati district, Tanzania, using the mother/baby field trial approach with a randomized complete block experimental layout. The trials were carried out over two annual production seasons to study the yield and profitability performance of elite vegetable cultivars grown under selected integrated management practices (IMPs), namely: healthy seedlings, good agronomic practices, and integrated pest management in comparison with standard farmer practices (SFPs). Input-output data from 16 plots showed that IMPs led to significant yield and profit increase (p<0.001) of up to 64.40 t ha-1 compared to 28.28 t ha-1 with a benefit-cost ratio (BCR) of 8.5 for tomato, and 53.45 t ha-1 compared to 23.04 t ha-1 (BCR=4.50) for African eggplant. Good quality seeds of improved cultivars were found to add 50 t ha-1 to tomato and African eggplant yields, with healthy seedlings adding a further 30 t ha-1 to the total yield compared to the control. IMPs significantly reduced (p<0.005) pest and disease incidence for tomato and African eggplant as well as reducing the frequency and quantity of chemical pesticides applied from 0.045 to 0.012 t ha-1, a good sign of environmental compliance.